PELATIHAN PENGUATAN LITERASI SAINS UNTUK ANAK SEKOLAH DASAR DESA MANYARSIDORUKUN GRESIK - Siti Amaliati; Ismawati Ismawati (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
This research advocates for an instructional approach that involves optimizing children's sensory engagement through the direct experiential exploration to enhance effective learning. By providing opportunities for hands-on learning experiences, this method aims to assist children in developing analytical skills and critical thinking abilities. Critical thinking skills are crucial for children to confront future challenges. Cultivating critical thinking by enhancing scientific literacy in children involves helping them grasp scientific concepts, observe natural phenomena, conduct experiments, and understand scientific processes. This enables children to develop their critical thinking abilities. However, many schools face challenges in facilitating experimental learning due to various factors and reasons. Therefore, this Community Engagement Initiative focuses on empowering elementary school-aged children by strengthening their scientific literacy through the introduction of